A new Moenkhausia (Characiformes: Characidae) from rio Braço Norte, rio Tapajós basin, with comments on the fish endemism of Serra do Cachimbo plateau - Lima, Arthur De; Vita, George; Dutra, Guilherme M.; Ohara, William M.; Pastana, Murilo N. L. (Zootaxa, 2023)
A new species of Moenkhausia is described from the rio Braço Norte, a tributary of Rio Teles Pires draining the Serra do Cachimbo, rio Tapajós basin, Pará, Brazil. The new species is diagnosed from all congeners, except M. moisae and M. pirauba, by having a high number of scales in the longitudinal series (43–46 vs. 23–41 in other Moenkhausia species). It can also be distinguished from the aforementioned species based on the combination of the following characters: a single humeral blotch, 21–25 branched anal-fin rays, and a round and symmetrical caudal blotch not continuous anteriorly with the dark midlateral stripe. The new tetra herein described represents an additional, possibly endemic, taxon from the headwaters draining from Serra do Cachimbo, in the Brazilian Shield.